Primary Aldosteronism and Drug Resistant Hypertension: A “Chicken-Egg” Story - Lenzini, L; Pintus, G; Rossitto, G; Seccia, T M; Rossi, G P (Experimental and Clinical Endocrinology & Diabetes, 2023)
Drug-resistant arterial hypertension (RH) is a major risk factor for cardiovascular disease, often due to overlooked underlying causes. Identification of such causes poses significant clinical challenges. In this setting, primary aldosteronism (PA) is a frequent cause of RH and its prevalence in RH patients is likely higher than 20%.The pathophysiological link between PA and the development and maintenance of RH involves target organ damage and the cellular and extracellular effects of aldosterone excess that promote pro-inflammatory and pro-fibrotic changes in the kidney and vasculature.The feasibility of adrenal vein sampling in PA patients with RH, and the clinical benefit achieved by adrenalectomy, further emphasize the need to implement systematic screening for this common form of secondary hypertension in the management of a high-risk population as RH patients.We herein review the current knowledge of the factors that contribute to the RH phenotype with a focus on PA and discuss the issues regarding the screening for PA in this setting and the therapeutic approaches (surgical and medical) aimed at resolving RH caused by PA.
Keywords: primary aldosteronism; drug resistant hypertension; mineralocorticoid receptor antagonists